Thailand - Simmons, Walter (Walter G.) (Minneapolis, MN : Bellwether Media, 2011)
Describes the geography and culture of Thailand, including information on such topics as the land, wildlife, people, food, and holidays of the country.
Where is Thailand? -- The land -- The Chao Phraya River -- Wildlife -- The people -- Daily life -- Going to school -- Working -- Playing -- Food -- Holidays -- Long live the king!.
Includes bibliographical references (p. 31) and index.
4.6
3-6
Keywords: Thailand -- Juvenile literature; Thailand -- Social life and customs -- Juvenile literature; Thailand; Thailand -- Social life and customs; Thailand; Thailand -- Social life and customs; Thailand